Analisis Tingkat Pertumbuhan Perumahan (Studi Kasus : Kecamatan Natar dan Kecamatan Jati Agung) - Bukka, Chiko Cristian Haganta; Syam, Tamaluddin; Putri, Marsista Buana (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) ITERA, 2023)
Population growth and new activity center development give impact on enhancement of residential demand. That demand always improves without be accompanied land availability and that can impact urban sprawl. The research locations are Natar and Jati Agung Sub-district which are designated as urban housing area, located on the outskirts of Bandar Lampung City. Activities will encourage the growth of demand of the private residential property thus this also encourage the building of residential area. The purpose of the research is to identify residential growth rate in the research locations. The research is conducted by using deductive approach. Data is collected by observation, interview, and literature review. Data is analyzed by using spatial analysis methods, nearest neighbor analysis, qualitative and quantitative descriptive analysis. The result of research explains that the highest residential growth rate in Natar Sub-district is 109.44% in 2017 and in Jati Agung Sub-district is 110.50% in 2019. Cluster residential pattern in Natar Sub-district with distribution index value (T) is 0.760346 tends to grow on the primary arterial road. While the same pattern shown in Jati Agung Sub-district with the distribution index value (T) is 0.817923 and tends to grow among new activities center in the South of Jati Agung Sub-district.